The origins and impact of state force - Miladinović Zalaznik, Mira (Acta neophilologica, 2013)
Working without a theoretical background the article discusses two Slovenian intellectuals: Angela Vode and Igor Šentjurc. These two writers and publicists, though separated by sex and the centuries in which they were born,are bound by life experience, for the state and Party, along with its subordinates, the Secret Police (Geheim-Polizei), as well as legal authorities that oppressed them, were fundamentally and continually a part of these two individuals' lives.
Keywords: German literature; German-language literature; nemška književnost; secret police; Slovene literature; slovenska književnost; Šentjurc, Igor, 1927-1996; tajna policija; Vode, Angela, 1892-1985; women in today's world; žensko vprašanje